2000
DOI: 10.1139/t00-008
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic liquefaction of loose gassy sand

Abstract: Gas can be found in many soils, but none more common than in seabed soils. Gas-charged sediments are known to be widely distributed throughout the world's oceans. Numerous research programs have studied saturated soil response to cyclic loading; however, little is known about the behavior of gassy soils subjected to cyclic loading. The response of loose gassy specimens subjected to cyclic loading was studied in a laboratory program. Triaxial tests were performed on specimens of reconstituted Ottawa sand prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…According to the past studies (e.g., Yoshimi et. al., 1989;Grozic et al, 1999), when the pore pressure coe‹cient B-value drops to zero level, the degree of saturation decreases by about 90z. Also in this research, the pore pressure coe‹cient Bvalues before cyclic shear were very small in comparison with the full saturation case shown in Table 1.…”
Section: Stress-strain Relationships Ešective Stress Paths and Suctimentioning
confidence: 99%
“…According to the past studies (e.g., Yoshimi et. al., 1989;Grozic et al, 1999), when the pore pressure coe‹cient B-value drops to zero level, the degree of saturation decreases by about 90z. Also in this research, the pore pressure coe‹cient Bvalues before cyclic shear were very small in comparison with the full saturation case shown in Table 1.…”
Section: Stress-strain Relationships Ešective Stress Paths and Suctimentioning
confidence: 99%
“…Therefore, due to high compressibility of the pore fluid, the amount of seismically induced excess pore pressure in a partially saturated soil can be significantly lower than that induced in the same soil at full saturation. This increase in liquefaction strength due to incomplete saturation has been proven experimentally [1][2][3][4][5]. For instance, cyclic triaxial tests conducted on Ottawa sand samples [1,2] confirmed that the presence of gas in partially saturated soils could enhance the liquefaction resistance of the soil samples expressed in terms of cyclic resistance ratio (CRR) by 200-300%.…”
Section: Introductionmentioning
confidence: 64%
“…This increase in liquefaction strength due to incomplete saturation has been proven experimentally [1][2][3][4][5]. For instance, cyclic triaxial tests conducted on Ottawa sand samples [1,2] confirmed that the presence of gas in partially saturated soils could enhance the liquefaction resistance of the soil samples expressed in terms of cyclic resistance ratio (CRR) by 200-300%. Other researchers have obtained similar results for the soil resistance against liquefaction due to partial saturation [3][4][5].…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Their main components include methane, carbon dioxide, and nitrogen (Figure 2). The gases mostly exist in the pores as dissolved or discrete bubbles (Wheeler, 1986;Grozic et al, 2000;Sánchez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%